MODELING OF ELECTRICAL PROPERTIES OF SOLID HETEROSTRUCTURES AND CERAMICS BASED ON SILICON CARBIDE - A. B. Cheboksarov; B. A. Kazarov; V. A. Cheboksarov (Современная наука и инновации)
In this paper, methods for calculating, analyzing, and mathematical modeling of electrical properties and characteristics of structures and ceramic semiconductor materials based on silicon carbide are considered. The advantages of the MDFG method -dynamic Green functions, Kubo-Greenwood formulas, and their application to mesoscopic and size effects, Anderson carrier localization, Mott transitions are formulated: the giant dielectric constant gain effect (SiC-AIN), the concentration dependence of conductivity (SiC-AIN, SiC- BeO) et al. In order to conduct a detailed study of the electrical properties and characteristics of semiconductor materials, it becomes necessary to study the behavior of the dielectric constant in ceramic jets SiC-AIN textures.